Long‐term urogenital assessment after elective laparoscopic sigmoid resection for diverticulitis: a comparison between central and peripheral vascular resection. (13th January 2021) - Posabella, Alberto; Varathan, Nadshathra; Steinemann, Daniel Christian; Göksu Ayçiçek, Selin; Tampakis, Athanasios; von Flüe, Markus; Droeser, Raoul André; Füglistaler, Ida; Rotigliano, Niccolò
Abstract: Aim: Increasing attention has been given to postoperative gastrointestinal functional outcome and quality of life after sigmoid resection for diverticulitis. Conversely, very little has been described about postoperative urogenital functional outcome and even less about its potential relationship to the type of vascular approach. The aim of this study was to evaluate whether central ligation of the inferior mesenteric artery (IMA) compared with peripheral dissection could impair urinary and sexual function in the long term. Method: Patients undergoing elective laparoscopic sigmoid resection for diverticulitis from 2004 to 2017 were retrospectively analysed. They were asked to complete the American Urological Association Symptom Index (AUASI) questionnaire. Men received the five‐item version of the International Index of Erectile Function (IIEF‐5) questionnaire. Patients were then divided according to the type of vascular resection. Results: A response rate of the 36.4% to the AUASI and 43.8% to the IIEF‐5 questionnaires was achieved. Three hundred and twenty four patients with a mean age of 62 ± 9.85 years were analysed for their urinary function (IMA preserved n  = 217; IMA resected n  = 107) in a median follow‐up of 87 months. Furthermore, 115 men with a mean age of 60 ± 8.97 years were investigated for their sexual function (IMA preserved n  = 80; IMA resected n  = 35) in a median follow‐up of 89 months. No difference (AUASI: 8 ± 6.32 IMA preserved vs. 7 ± 6.26 IMA resected, P  = 0.204; IIEF‐5: 15 ± 7.67 IMA preserved vs. 15 ± 8.61 IMA resected, P  = 0.674) was found regarding the type of vascular approach during sigmoid resection. Conclusions: No association was found between the type of vascular approach and the long‐term urogenital functional outcome in patients undergoing sigmoid resection for diverticulitis. Abstract : In surgery for diverticulitis the vascular dissection can be performed on sigmoid branches or with a resection of the inferior mesenteric artery due to the benign nature of the disease. Our study showed that the vascular approach does not affect the postoperative urogenital outcome.